Guinea : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
In 2003, Guinea's macroeconomic management deteriorated significantly, and the prospects for 2003 are uncertain at best. Performance under the 2002-03 poverty reduction and growth facility (PRGF)-supported program is weak. The main challenge is to promote and sustain the strong private sector-led growth that is necessary to achieve the poverty reduction objectives set out in the poverty reduction strategy paper (PRSP). IMF staff urged the authorities to adopt appropriate fiscal and monetary policies and step up the implementation of structural reforms.